ANALISIS PEMILIHAN SAHAM DALAM PEMBENTUKAN PORTOFOLIO EFISIEN PADA SAHAM YANG TERGABUNG DALAM LQ 45 - Achmad, Daniel Noor; Sahala, Bintang; Febriyanti, Devy (Jurnal Ilmiah Manajemen Kesatuan, 2015)
The purpose of this study is to determine what level of profit expected from each combination of portfolio and risk that exist on any combination of portfolio and detemine the allocation of capital to form an efficient portfolio. Selection of investment assets formed through historical data processing daily stock LQ 45 period from February to July 2012 Election assets in stocks LQ 45 because these stocks are illiquid stocks, that can be traded actively in the capital markets. Formation of eficient portfolio performed in an eficient portfolio in 2012 with the theoretical period of daily data and demonstrated in a realistic period of eficient portfolio in 2013 with the same asset allocation but generate returns and different risks. Based on the results of the calculations have been done, it can be concluded that the 5 pairs best portfolios. Keywords: Return, Risk, Efficient Portfolios